Model of the Need for Road Service Improvement, Maruni Manokwari, Indonesia - Parlindungan, Charlton; Mudjanarko, Sri Wiwoho; Setiawan, Muhammad Ikhsan; Wahyuni, Atik (Malikussaleh University, Aceh, Indonesia, 2023)
Roads are vital infrastructure for land transportation and one of the most critical aspects of development in the national and regional economy. According to the Central Statistics Agency for West Papua, the roads successfully built in West Papua Province were only 11,951,592 km until 2017. It comprises 1003.26 km, 2309,648 km, and 8,638,687 km of national, provincial, and regency roads, including Jalan Maruni - Manokwari City Limits. According to the Minister of PU-PR RI, this road type 2/2 UD length is 17.17 km and administratively connects two districts (West and South Manokwari). One of the areas in West Papua Province where the development of infrastructure, investment, and urbanization is very rapid is Manokwari Regency. In line with the change in government status, its development then changed the physical image of the region to become urban. It is because Sorong City has a strategic economic location concerning natural resources, high accessibility, and is the center of the provincial government, thus attracting other financial functions for investment. This movement burdens road infrastructure, and we need several alternative treatments to improve the service of the street segment above. The method is done through surveys of stakeholders on alternative handling, and then the results are analyzed using multiple linear regression. This research is expected to find alternative handling solutions to improve road services in this segment.